Perbandingan Titik Lunak Resin Damar Mata Kucing dengan Resin Damar Batu - Suherbowo, Natania Ramadhiani; Usri, Kosterman; Hidayat, Opik Taopik (Jurnal Material Kedokteran Gigi, 2021)
Resin is widely used in dentistry these days. But synthetic resin is mostly used, because natural resin production is considered expensive in western countries. Meanwhile Indonesia has potential natural resources and one of the world’s natural resin producers. Dammar resin is one of them, there are two kinds considered the best which is mata kucing dammar resin and batu dammar resin. There are different characteristics between the two resin because they came from different tree species. This research, Difference in Softening Point of Mata Kucing Dammar Resin and Batu Dammar Resin, aims to determine the difference  in the softening point of the two dammar resin so we can discover the use of dammar resin as one of the basic dental materials. Softening point test was done on 16 samples of mata kucing dammar resin and 16 samples of batu dammar resin using Ring and Ball Apparatus based on SNI 01-2900-1999. From the study results, it is obtained that the softening point of mata kucing dammar resin is 87-90°C, meanwhile batu dammar resin is 150-160°C.  Softening point is the temperature which when dammar resin starts to transform into semisolid. A high softening point temperature shows that the dammar resin has long hardened because the compound chemical bond is reduced as a result of oxidation reaction. Mata Kucing dammar resin is yellowish-clear is gotten by tapping directly into the Shorea javanica tree, meanwhile the batu dammar resin which is brownish-black is gotten by collecting the fossilized sap on the ground beneath the Shorea eximia tree. Therefore, the mata kucing dammar resin has less ash and dirt content. Mata kucing dammar resin and batu dammar resin have different softening point temperature.